Troponin I is an independent predictor of cardiovascular events and mortality in haemodialysis patients - Tydén, Maria; Westerlund, Magnus E; Duarte, Kevin; Eriksson, Niclas; Girerd, Nicolas; Krämer, Bernhard; März, Winfried; Rossignol, Patrick; Scharnagl, Hubert; Soveri, Inga; Svensson, Maria K; Zannad, Faiez; et al. (Clinical kidney journal, 2025)
Patients with end-stage kidney disease (ESKD) undergoing haemodialysis (HD) have a high risk of cardiovascular (CV) events. This study evaluated troponin I (hs-cTnI) as a predictor of major adverse cardiac events (MACEs), CV death and all-cause death.The AURORA trial, a multicentre, randomized, double-blind trial involved 2776 HD patients comparing rosuvastatin with placebo. No significant effect was found on the composite primary endpoint of CV death, non-fatal myocardial infarction or non-fatal stroke. In this post hoc analysis, we analysed the association between baseline hs-cTnI and outcomes using Cox regression analyses. We adjusted for multiple background factors and available biomarkers. Hs-cTnI was log2-transformed and modelled using a four-knot restricted cubic spline. Variables were ordered by their importance in the models using χ2 value minus degrees of freedom.Baseline median hs-cTnI was 17.3 pg/mL. During follow-up, 734 MACEs, 598 CV deaths, and 1094 total deaths occurred. Patients in the upper quartile of hs-cTnI (>32.6 pg/mL) had significantly higher risk of MACEs [hazard ratio (HR) 1.92; 95% confidence interval (CI) 1.57-2.35], CV death (HR 2.12; 95% CI 1.69-2.66), all-cause death (HR 1.84; 95% CI 1.55-2.17) and non-CV death (HR 1.59; 95% CI 1.23-2.05) after full adjustment compared with those in the lowest quartile (<10.1 pg/mL). Hs-cTnI was identified as the strongest predictor for MACEs, CV death, and all-cause death, but not for non-CV death.Baseline hs-cTnI is a strong and independent predictor for MACEs and death in patients with ESKD undergoing haemodialysis.
Online veröffentlicht: 11. Februar 2025
Gesehen am 01.07.2025